Cranial morphology reveals a lack of phylogenetic signal and rapid adaptive radiation in the bat genus Molossus (Chiroptera: Molossidae) - Ana Priscila Medeiros Olímpio; Fabiano Stefanello; Beatriz Dybas da Natividade; Itiberê Piaia Bernardi; Amanda Cristiny da Silva Lima; Samira Brito Mendes; Cleison Luís da Silva Costa; Elmary da Costa Fraga; Maria Claudene Barros; Iracilda Sampaio (PLoS ONE, 2025)
The 16 species of Molossus (Chiroptera: Molossidae) are distributed throughout the Neotropical region and can be classified into two groups: one consisting of morphologically similar yet phylogenetically divergent species, and another of morphologically distinct but closely related species. This dynamic has led to frequent revisions in the systematics and taxonomy of this genus. This study aimed to analyze patterns of diversification in cranial shape and size within Molossus species using geometric morphometrics (GM), integrating genetic and morphological data. A total of 299 specimens from ten Molossus species widely distributed across the Neotropics were examined, focusing on cranial size, shape diversity, and evolution, and correlating these findings with mitochondrial DNA-based phylogenetic data. Integrated morphometric and phylogenetic analyses revealed a complex evolutionary history within Molossus, with most speciation events occurring during the Pleistocene, suggesting a recent rapid adaptive radiation. GM analyses demonstrated patterns of divergence in cranial size with shape conservatism, and these traits were not significantly related to phylogeny. The data indicate that phylogenetic relationships have limited influence on cranial morphology due to the lack of a strong phylogenetic signal, suggesting that ecological factors, such as diet and habitat, have played central roles in the diversification of Molossus.